Sunlight-excited multi-ROS (reactive oxygen species) response oxygen sensitization type hydrogel as well as preparation method and application thereof
By using a sunlight-excited, multi-ROS-responsive oxygen-sensitizing hydrogel, combined with the synergistic effect of nano-thylakoids and photosensitizers, the problem of intelligent responsiveness and multi-mechanism synergy in the treatment of diabetic foot ulcers has been solved, achieving efficient and safe wound healing.
Patent Information
- Application Number
- CN202511427032.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2025-12-16
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical technology and relates to medical materials, specifically to sunlight-excited multi-ROS responsive oxygen-sensitizing smart hydrogel (NTALG) and its preparation method and application. Background Technology
[0002] Currently, there are three main strategies for using hydrogel materials to treat diabetic foot ulcers: photodynamic therapy, oxygen generation therapy, and antibacterial therapy. Photodynamic therapy uses photosensitizers to generate reactive oxygen species under light excitation to kill microorganisms and regulate inflammation; related hydrogels possess photothermal, photodynamic, and intelligent response properties. Oxygen generation therapy utilizes hydrogels to catalyze the decomposition of hydrogen peroxide or release oxygen to improve local oxygen supply; some also combine photothermal effects for antibacterial purposes. Antibacterial therapy controls infection through physical destruction, chemical sterilization, or drug sustained-release mechanisms; some hydrogels can synergistically clear bacteria and regulate inflammation, and some have characteristics such as self-healing and high adhesion.
[0003] Currently reported materials have shortcomings in terms of intelligent responsiveness, clinical translation, and multi-mechanism synergy. Regarding intelligent responsiveness, current materials do not adequately utilize the microenvironment of diabetic wounds. They largely fail to simultaneously utilize the characteristics of the microenvironment during diabetic ulcer healing, such as hypoxia and high bacterial load, to achieve intelligent responses. This results in a lack of targeted intelligent regulation at key stages of wound healing. In terms of clinical translation, clinical applications require materials to be well-compatible with human tissues and not trigger adverse reactions such as immune rejection. There are currently few reports on the biocompatibility of these materials, and the potential harm to humans from the materials and their degradation products during long-term use remains unclear, introducing uncertainty into clinical translation. Regarding multi-mechanism synergy, although some materials have achieved multi-mechanism synergy, such as the photothermal-enzymatic-oxygenation synergy of PPGW hydrogels, the overall synergistic mechanism is still not perfect. For example, in terms of antibacterial, anti-inflammatory, and pro-angiogenic multi-mechanism synergy, most materials simply combine different functions without a systematic synergistic design. There may be mutual interference between mechanisms or the inability to fully utilize their respective advantages, leading to suboptimal overall therapeutic effects. Furthermore, the treatment of diabetic ulcers is a dynamic process, with varying degrees of need for different treatment mechanisms at different stages. Current multi-mechanism synergistic materials lack the ability to dynamically regulate according to the ulcer healing process, and cannot simultaneously achieve antibacterial, oxygen-producing, angiogenesis-promoting, and tissue repair-enhancing effects to meet the complex and ever-changing clinical treatment needs. Summary of the Invention
[0004] Based on this, the purpose of this invention is to provide a sunlight-excited multi-ROS responsive oxygen-sensitizing hydrogel (NTALG), its preparation method and application. The hydrogel can simultaneously achieve antibacterial, oxygen production, and angiogenesis promotion, and enhance tissue repair function to meet the complex and ever-changing clinical treatment needs.
[0005] The technical solutions for achieving the above objectives include the following.
[0006] The first aspect of the present invention is to provide a sunlight-excited multi-ROS-responsive oxygen-sensitizing hydrogel, which is prepared from plant-derived nanothylakoids (NTs) and cationic liposomes loaded with 2-(4-(1,6,9-triphenyl-3a,11b-dihydro-1H-phenanthro[9,10-d]imidazol-2-yl)phenyl)anthracene-9,10-dione (AQPP) and Prönnick F127 as the hydrogel matrix.
[0007] In some embodiments, the nanothylakoids are derived from spinach.
[0008] In some embodiments, the method for preparing the AQPP-loaded liposomes includes the following steps: mixing the four components of total lipids in tetrahydrofuran (THF) solvent according to the simplest molar ratio, and simultaneously adding AQPP to obtain a mixed solution, wherein the concentration of total lipids in the mixed solution is 0.1-20 mg / mL, and the concentration of AQPP is 0.1-10 mg / mL;
[0009] Perform ultrasonic treatment;
[0010] Add the obtained solution dropwise to deionized water while stirring continuously;
[0011] Remove tetrahydrofuran, filter, and you have the product.
[0012] In some embodiments, the simplest molar ratio of the four components in the total lipids—dioyltrimethylammonium chloride (DOTAP), dioleoylphosphatidylethanolamine (DOPE), cholesterol, and dioleoylphosphatidylethanolamine-polyethylene glycol 2000 (DOPE-PEG2000)—is (0.125-2):1:1:0.05; in some embodiments, the simplest molar ratio of dioleoyltrimethylammonium chloride (DOTAP), dioleoylphosphatidylethanolamine (DOPE), cholesterol, and dioleoylphosphatidylethanolamine-polyethylene glycol 2000 (DOPE-PEG2000) is any one of the following: 0.25:1:1:0.05; 0.5:1:1:0.05; 1:1:1:0.05;
[0016] 2:1:1:0.05.
[0017] In some implementations, the most preferred ratio is 1:1:1:0.05.
[0018] In some embodiments, the concentration of total lipids is 0.5-10 mg / mL, 1-3 mg / mL, or 1.5-2.5 mg / mL.
[0019] In some embodiments, the concentration of AQPP is 0.5-5 mg / mL, 0.5-2 mg / mL, or 0.8-1.2 mg / mL.
[0020] In some embodiments, the mass ratio of total lipids to AQPP is (1-3):1, more preferably (1.5-2.5):1, and most preferably 2:1.
[0021] A second aspect of the present invention is to provide a method for preparing a photoexcited multi-ROS responsive oxygen-sensitizing hydrogel.
[0022] A method for preparing a photoexcited, multi-ROS-responsive, oxygen-sensitizing hydrogel includes the following steps:
[0023] S1: Disperse NT in deionized water at a chlorophyll concentration of 10-1000 μg / mL to obtain an NT aqueous solution, add Prönkel F127 to obtain an NT hydrogel; disperse AL in deionized water at a concentration of 10-1000 μg / mL to obtain an AL aqueous solution, add Prönkel F127 to obtain an AL hydrogel.
[0024] S2: NT hydrogel and AL hydrogel are mixed and sprayed in a volume ratio of 1:1 at a temperature range of 4℃-25℃ and formed in situ on the surface at 34℃-36℃.
[0025] In some implementations, the mixture is mixed and sprayed into a dual-channel spray bottle.
[0026] In some preferred embodiments, the concentration of NT in the NT aqueous solution is 80-120 μg / mL, more preferably 100 μg / mL, and the concentration of AL in the AL aqueous solution is 100-300 μg / mL, more preferably 150-250 μg / mL, and even more preferably 200 μg / mL.
[0027] In some embodiments, the content of Prönnik F127 in the NT hydrogel and AL hydrogel is 10-25 wt%, preferably 15 wt%-25 wt%, and more preferably 17 wt%-20 wt%.
[0028] A third aspect of the present invention is to provide the use of the aforementioned sunlight-excited multi-ROS-responsive oxygen-sensitizing hydrogel in the preparation of a medicament for treating skin ulcers.
[0029] In some embodiments, the skin ulcer is a diabetic foot ulcer.
[0030] This invention provides a sunlight-excited multi-ROS-responsive oxygen-sensitizing hydrogel (NTALG), which encapsulates a biphenyl ring-modified phenanthrimidazole derivative AQPP photosensitizer into a permanently positively charged liposome (AL). Utilizing a ROS bactericidal and oxygen-sensitizing strategy, it simultaneously achieves antibacterial, oxygen-generating, and angiogenesis-promoting effects, enhancing tissue repair functions to meet the complex and ever-changing clinical treatment needs.
[0031] Synergistic effect of oxygen self-supply and photodynamic therapy: Through the synergistic reaction of NT and AL, the bottleneck of traditional photodynamic therapy being limited by hypoxia is broken.
[0032] Bacterial biofilm adsorption, multiple ROS response logic: Integrating positive and negative charge adsorption, oxygen-sensitized type II photochemical reaction ROS generation mechanism, to achieve precise matching of drug release and efficient killing of drug-resistant bacteria.
[0033] Sprayable and adaptable: The F127-based spray formulation simplifies clinical procedures and is suitable for deep and irregular wounds.
[0034] This invention provides a sunlight-excited multi-ROS responsive oxygen-sensitizing hydrogel (NTALG) as an efficient, safe, and intelligent solution for the treatment of diabetic wounds. Attached Figure Description
[0035] Figure 1 This is a schematic diagram of the preparation and characterization of NT and AL.
[0036] Figure 2 This is a schematic diagram of the preparation and characterization of NTALG.
[0037] Figure 3 This is a schematic diagram showing the in vitro anti-MRSA and anti-Ecoli activity results of NTALG.
[0038] Figure 4 This is a schematic diagram showing the in vivo wound healing capacity of NTALG in diabetic patients.
[0039] Figure 5 This is a schematic diagram of the NTALG biosafety assessment results.
[0040] Figure 6 This describes the gelation of NTALG at 20°C and 35% body surface temperature under five different F127 ratios: 10%, 15%, 17%, 25%, and 30%.
[0041] Figure 7 This is a statistical graph showing the particle size and polydispersity index of AL liposomes obtained with different phospholipid ratios.
[0042] Figure 8 This is a schematic diagram of a dual-channel spray bottle. Detailed Implementation
[0043] To facilitate understanding of the present invention, a more complete description will be provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0044] Unless otherwise specified, experimental methods in the following examples are generally performed under standard conditions or as recommended by the manufacturer. All commonly used chemical reagents used in the examples are commercially available products.
[0045] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used in this invention includes any and all combinations of one or more of the associated listed items.
[0046] This invention, through the technical concept of material system design and functional integration, has obtained a hydrogel whose main components are NT and AL.
[0047] To meet the needs of clinical applications, Pluronic F127, which has temperature responsiveness, was selected as the hydrogel matrix. Its sol-gel phase transition properties (liquid at low temperatures, solid at body temperature) enable convenient application and adaptive film formation of wound sprays. By adjusting the concentration of Pluronic F127 (20wt%-30wt%), the adhesion and protection to irregular wounds are ensured.
[0048] 2-(4-(1,6,9-triphenyl-3a,11b-dihydro-1H-phenanthro[9,10-d]imidazol-2-yl)phenyl)anthracene-9,10-dione (AQPP) has the following structural formula:
[0049] This compound can be prepared and identified by the method disclosed in Chinese patent CN118271247A.
[0050] To endow hydrogels with oxygen-generating capabilities and utilize the synergistic effect of oxygen and the photosensitizer AQPP to produce singlet oxygen, we extracted and modified nanoscale thylakoids (NTs) from plants. These NTs contain embedded photosystem II (PSII) complexes that catalyze water splitting under sunlight excitation, continuously releasing oxygen (O2) to alleviate the hypoxic microenvironment caused by vascular damage in diabetic wounds. Simultaneously, Pluronic F127 encapsulation enhances the stability of the NTs. The released oxygen achieves a photodynamic synergistic effect.
[0051] This invention encapsulates the biphenyl ring-modified phenanthreneimidazole derivative AQPP photosensitizer into a permanently positively charged liposome (AL), which, upon excitation by sunlight (400-700 nm), generates multiple ROS such as hydroxyl radicals. • OH), superoxide anion (O2) •- ) and singlet oxygen ( 1 O2) maximizes photodynamic antibacterial activity (killing rate of >99% against Staphylococcus aureus and Escherichia coli).
[0052] 1. Multiple response mechanisms and dynamic regulation
[0053] Sunlight-triggered cascade reaction: Under sunlight irradiation, NT oxygen production and AQPP photosensitizer activation form a synergistic chain reaction:
[0054] Electrostatic adsorption: Positively charged liposomes autonomously adsorb to negatively charged bacterial biofilms;
[0055] Photodynamic antibacterial: AQPP absorbs light energy to generate ¹O2, which directly destroys bacterial biofilms and DNA;
[0056] Oxygen self-supply: NT decomposes water to produce oxygen, overcoming the efficacy reduction caused by hypoxia in traditional photodynamic therapy, while promoting wound healing.
[0057] 2. Technical Effects and Data Support
[0058] Antibacterial and angiogenesis-promoting effects: In vitro experiments showed that this hydrogel achieved a 98.5% clearance rate of MRSA biofilm (24 hours) and upregulated the expression of vascular endothelial growth factor (VEGF) by 2.3 times.
[0059] Wound healing verification: In a full-thickness skin defect model in diabetic rats, the wound closure rate in the treatment group reached 95% after 14 days, which was significantly higher than that in the control group (70%). The density of newly formed capillaries increased by 2 times, and the collagen arrangement was close to that of normal skin.
[0060] Safety assessment: The cytotoxicity assay (CCK-8) showed that the hydrogel had a fibroblast survival rate of >95%, which meets the standards for biomedical materials.
[0061] The present invention will be further described in detail below with reference to specific embodiments.
[0062] Example 1
[0063] Preparation of nanothylakoids (NTs):
[0064] NT was isolated from fresh spinach according to a previously reported method (J. Ouyang, L. Wang, W. Chen, K. Zeng, Y. Han, Y. Xu, et al. Chemical Communications 2018 Vol. 54 Issue 28 Pages 3468-3471 DOI: 10.1039 / C8CC00674A). Specifically, 100 g of spinach leaves were washed and then left overnight at 4°C. Subsequently, the spinach leaves were homogenized in a juicer with 300 mL of pre-cooled homogenization buffer (20 mmol of tris(hydroxymethyl)glycine, 0.4 mol of sucrose, 2 mmol of ascorbic acid, 2 mmol of magnesium chloride, 40 mmol of sodium chloride, 0.2% bovine serum albumin (BSA), pH 7.8). The leaf fragments were then filtered three times through ten layers of gauze, and the filtrate was collected. The filtrate was then centrifuged at 600 g for 5 minutes. The supernatant was then centrifuged at 1500 g for 10 minutes to collect intact chloroplasts. The precipitate was resuspended in hypotonic lysis buffer (10 mmol / L 4-(2-hydroxyethyl)-1-piperazine ethanesulfonic acid (HEPES), 10 mmol / L sodium chloride, 5 mmol / L magnesium chloride, pH 7.6) for 2 hours, followed by centrifugation at 8000 rpm for 10 minutes to remove matrix extract from the supernatant. The precipitate containing thylakoids was collected and washed twice with 10 mmol / L HEPES buffer. Finally, the thylakoids were suspended in water and sonicated at 4 °C for 5 minutes (6Φ, 200 W). The thylakoid lumen extract was removed by centrifugation at 16000 rpm for 15 minutes, yielding a dark green thylakoid membrane precipitate. To prepare nanothylakoids (NTs), thylakoid membranes were dispersed in phosphate-buffered saline (PBS, pH = 7.4). After sonication for 5 minutes, the mixture gradually became clear and was then extruded through a 200 nm porous polycarbonate membrane to obtain nanothylakoids.
[0065] Chlorophyll concentration is calculated using the following formula:
[0066] Chlorophyll a (µg / mL) = 13.95 × A665 - 6.88 × A649 (Formula 1)
[0067] Chlorophyll b (µg / mL) = 24.96 × A649 - 7.32 × A665 (Formula 2)
[0068] Total chlorophyll (µg / mL) = Chlorophyll a + Chlorophyll b (Formula 3)
[0069] Wherein, A649 and A665 represent the absorbance of the nanothylakoids at 649 nm and 665 nm, respectively.
[0070] Preparation of AQPP liposomes (AL):
[0071] The lipid components dioleoylphosphatidylethanolamine (DOPE), cholesterol, dioleoylphosphatidylethanolamine-polyethylene glycol 2000 (DOPE-PEG2000), and the positively charged lipid dioleoyltrimethylammonium chloride (DOTAP) were mixed in tetrahydrofuran (THF) solvent at the simplest molar ratio, with AQPP added simultaneously. The total lipid concentration of the lipid membrane in the mixture was 2 mg / mL, and the concentration of AQPP in the mixture was 1 mg / mL. The mixture was then subjected to ultrasonic treatment. The simplest molar ratio of the lipid components was any of the following: 0.125:1:1:0.05; 0.25:1:1:0.05; 0.5:1:1:0.05; 1:1:1:0.05;
[0076] 2:1:1:0.05.
[0077] The resulting solution was then added dropwise to 15 mL of deionized water under magnetic stirring at 45 °C and 1000 rpm for 1 hour. Next, tetrahydrofuran was removed from the original AL dispersion using a rotary evaporator at a vacuum of 0.1 MPa. The liposome suspension was filtered through a 0.22 μm sterile filter. Finally, the AL dispersion was stored at 4 °C for later use.
[0078] The concentration of AQPP was calculated by measuring the absorbance at a wavelength of 333 nm using a UV spectrophotometer.
[0079] Extraction and determination of total protein from leaves, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE).
[0080] At 4°C, 0.5 g of spinach leaf tissue was homogenized with 3 mL of buffer in a pre-chilled mortar. The buffer contained 50 mmol of tris(hydroxymethyl)aminomethane (Tris) and glycine (pH 8.3), 0.5 mmol of sucrose, 50 mmol of EDTA, 0.1 mmol of potassium chloride (KCl), 2 mmol of PMSF, and 0.1% (v / v) of 2-mercaptoethanol. The homogenate was centrifuged at 14000 g for 10 min in a refrigerated centrifuge (Sigma 2K15, Germany). The protein concentration in the supernatant was determined according to Bradford's method (1976), and the sample was aliquoted and stored at -85°C for SDS-PAGE analysis. Thylakoids (NTs) and leaf homogenate were dispersed in loading buffer (Beyotime Biotechnology). Then, heat the loading buffer to 90°C and maintain this temperature for approximately 10 minutes. Afterward, add the samples accordingly to the wells of a 12% bis(tris(hydroxymethyl)aminomethane) (Bis-Tris) gel. Perform protein staining using Coomassie Brilliant Blue (Beyotime).
[0081] Preparation of NT, AL or NTAL hydrogels
[0082] Preparation of NT or AL hydrogels: NT was dispersed in deionized water at 100 μg / mL, and AL was dispersed in deionized water at 40 μg / mL. Subsequently, NT- or AL-based hydrogels were prepared by dissolving Pluronic F127 in NT or AL solutions at different mass ratios (10%, 15%, 17%, 25%, 30%) at 0℃–4℃. A hydrogel composed of Pluronic F127 and deionized water was used as a control. The hydrogels were then stored in a refrigerator at 4℃ overnight to allow complete dissolution.
[0083] Preparation of NTAL hydrogel: After obtaining two hydrogels based on NT and AL, equal volumes of NT and AL hydrogels are mixed during spraying through the channels of a dual-channel spray bottle. The hydrogels are then stored in a refrigerator at 4°C. Specifically, the NT and AL hydrogels are stored in a dual-chamber spray bottle and remain liquid between 4°C and 20°C. When using, the hydrogels are removed from the refrigerator, and the spray nozzle is pressed at any pressure (a commonly used and suitable pressure range is 0.05-0.3 bar (5-30 kPa)). NT and AL are mixed 1:1 in the spray bottle until they are sprayed as a mist. Finally, the hydrogel spray is splashed onto the skin at a surface temperature of 35°C to form an in-situ NTAL hydrogel mixture.
[0084] Detection of total reactive oxygen species (ROS) generation
[0085] To prepare the stock solution, dichlorodihydrofluorescein diacetate (DCFH-DA, 0.5 mL, 1 mmol / L ethanol solution) was first reacted with 2 mL of 10 mmol / L sodium hydroxide aqueous solution at room temperature for 30 min. Then, the resulting hydrolysis products were neutralized with 10 mL of phosphate-buffered saline (PBS) to obtain a final solution with a concentration of 40 μmol / L. For the preparation of the test solution, 30 μL of nanothylakoids (NT), AQPP liposomes (AL), and the NT and AL complex (NTAL) were added to 2970 μL of DCFH solution with the same integrated absorption area. The mixture was then exposed to white light at a power density of 60 mW / cm². The DCFH fluorescence signal, used to assess the reactive oxygen species (ROS) generation rate, was detected at an excitation wavelength of 488 nm and an emission wavelength of 530 nm.
[0086] Singlet oxygen ( 1 Detection of O2)
[0087] 2940 μL of PBS buffer, 30 μL of 9,10-anthracite dipropionic acid (ABDA, 10 mmol / L methanol solution), and 30 μL of NT, AL, or NTAL with the same integral absorption area were mixed. After irradiation with white light at a power density of 60 mW / cm², the absorption signal of the indicator was monitored. A decrease in the absorption signal at 400 nm indicated singlet oxygen (…). 1 The generation rate of O2.
[0088] Superoxide anion radical (O2) •- Detection of hydroxyl radicals (•OH) and hydroxyl radicals (•OH)
[0089] 2940 μL of PBS buffer, 30 μL of dihydrorhodamine 123 (DHR123) / hydroxyl radical fluorescent probe (HPF) (1 mmol / L methanol solution), and 30 μL of NT, AL, or NTAL hydrogel with the same integral absorption area were mixed. After irradiation with white light at a power density of 60 mW / cm², the fluorescence signal of the indicator was monitored to indicate superoxide anion radicals (O₂) at excitation wavelengths of 488 / 450 nm and emission wavelengths of 527 / 515 nm. •- The rate of generation of hydroxyl radicals (•OH).
[0090] Oxygen generation detection of NT or NT hydrogel, AL hydrogel and NTAL hydrogel
[0091] To compare the oxygen production of NT, NT was placed in PBS, and dissolved oxygen was removed with nitrogen. Then, after removing dissolved oxygen with nitrogen, the oxygen production was measured using a microelectrode under light illumination. To compare the oxygen production of NT hydrogel, AL hydrogel, and NTAL hydrogel, the hydrogels were first heated until they solidified in a glass bottle. Then, 3 mL of deionized water was added. The light path was then adjusted so that it passed vertically through the bottom of the glass bottle, and the oxygen production was measured using a microelectrode under light illumination.
[0092] Characterization of NT, AL, or NTAL hydrogels:
[0093] Determine the gelation temperature and time of NT, AL, or NTAL hydrogels. Place a bottle containing 2 mL of liquid hydrogel in a water bath and heat. Record the temperature and time when the solution stops flowing to determine the gelation time and temperature. Determine the chemical composition and structure of NT, AL, or NTAL hydrogels using a Fourier transform infrared spectroscopy (FTIR, Thermo Fisher Scientific, Nicolet™ iS50) in the 600–4000 Å scan range, with 32 scans and a resolution of 40 Å. Evaluate the rheological properties of NT, AL, or NTAL hydrogels using a rheometer (Thermo Fisher Scientific, HAAKE™ MARS™).
[0094] Release study of AL hydrogel
[0095] To investigate the release of liposomes from the hydrogel, 0.5 mL of hydrogel was poured into 50 mL centrifuge tubes. The tubes were then incubated at 37°C to allow gel formation, and 50 mL of deionized water (pH 8.5 / 7.5 / 4.5) was added to each tube under gentle shaking. At predetermined time points, 500 μL of liquid was collected from each tube. To quantify the amount of liposomes released from the hydrogel, an 80% tetrahydrofuran (THF) solution of the collected liquid was prepared. The fluorescence intensity of the samples was quantified using a fluorescence spectrophotometer (Horiba Corporation, Canada, Duetta model) at an excitation wavelength of 333 nm and an emission wavelength of 436 nm.
[0096] Cytotoxicity and migration
[0097] The cytotoxicity of the hydrogel was assessed using human immortalized keratinocytes (HaCaT) via the MTT assay. Cells were seeded into the lower chamber of a 24-well Transwell plate (100 cells per well) and cultured for 12 hours. NTAL hydrogel was then added to each upper chamber, and the cells were incubated for another 12 hours. MTT solution was then added, and the cells were incubated for another 2 hours. Absorbance at 490 nm was measured using a standardized procedure. Furthermore, calcein-AM (mol / L) and propidium iodide (PI) staining were used to differentiate between live and dead cells. For cell migration assays, 100 HaCaT cells were seeded into 24-well plates and allowed to grow for 24 hours before scratch treatment. A uniformly wide line was then drawn in the center of each well using a 100 μL pipette to remove cells from that area. Cells were then placed in different environments and divided into four groups: a hypoxic environment group, an oxygen-supported environment group, a hypoxic environment group co-incubated with NTAL hydrogel, and a hypoxic environment group co-incubated with NTAL hydrogel and exposed to light. Cell migration was then recorded at 12 and 24 hours.
[0098] Experimental results:
[0099] 1. Preparation and characterization of NT and AL
[0100] First, the materials NT and AL were prepared according to previously reported methods. Figure 1 A and Figure 1 D describes the preparation methods of NT and AL. For example... Figure 7As shown, AL was prepared by mixing DOATP and DOPE in five different molar ratios, and dynamic light scattering analysis was performed on the AL. With increasing DOATP content, the particle size initially decreased and then increased, while the polydispersity index showed the same trend. To ensure that AL could penetrate the hydrogel pores, we selected a combination of formulations with a hydrated particle size less than 100 nm.
[0101] The following experimental results were obtained by using the simplest molar ratio of the four components in total lipids of 1:1:1:0.05.
[0102] Figure 1 B and Figure 1 E indicates that the hydrated particle sizes are approximately 250 nm and 90 nm, respectively. The concentrated particle size indicates uniformity; the ZETA potentials are -23.8 mV and +18.8 mV, respectively. Transmission electron microscopy (TEM) revealed the membrane structure of NT and the liposome-like structure of AL. Figure 1 C and Figure 1 F characterizes the normalized absorption and emission spectra of NT and AL. From Figure 1 The UV-VIS absorbance spectrum in C shows that NT exhibits absorption bands at 435 and 676 nm, which are attributed to the porphyrin moiety of chlorophyll. Furthermore, the fluorescence spectrum reveals a characteristic emission peak of chlorophyll at 687 nm. On the other hand, from... Figure 1 The UV-VIS absorbance spectrum in F shows that AL exhibits an absorption band at 333 nm and a maximum emission peak at 436 nm.
[0103] Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) showed that NTs preserve most membrane proteins on the thylakoid membrane. Figure 1 G). Next, we studied the oxygen production curve of NT within 10 minutes under xenon lamp irradiation (60mW) mM. Figure 1 H characterizes the oxygen production curve of thylakoids and reveals the oxygen production mechanism. Compared with the control group, NT reached the maximum oxygen production of 1.5 mg / L at 7 minutes after irradiation. Figure 1 I presents a schematic diagram illustrating the mechanism by which AQPP photosensitizer generates reactive oxygen species upon light exposure. Electron paramagnetic resonance results indicate that AL can generate singlet oxygen and hydroxyl radicals upon light exposure. Figure 1 J). For example Figure 1 As shown in Figure J, AL can induce a strong ESR signal after white light illumination, indicating the generation of a large amount of ESR signal. 1 O2 and • OH. Based on the above evidence, we can conclude that AL underwent a type II PDT energy transfer process to produce 1•O2, and also possesses the ability to generate type I ROS free radicals. The ROS generation capacity of NTAL has been thoroughly studied using various ROS indicators, including dichlorodihydrofluorescein (DCFH, a total reactive oxygen species probe), 9,10-anthratridiyl-bis(methylene)dimalonic acid (ABDA, a type of...). 1 O2 indicator), dihydrorhodamine 123 (DHR123 O2) •- Indicators) and hydroxyphenylfluorescein (HPF, •OH indicator). In the ROS generation capacity experiment, NTAL is an aqueous solution of NT and AL directly mixed, with NT concentrations of 15 μg / mL and AL concentrations of 15 μg / mL, respectively. Figure 1 As shown in K, under the same conditions, the total ROS production efficiency of NATL is 1.28 times that of AL alone. 1 O2 production is 1.3 times that of AL and 1.67 times that of NT. NATL's O2 •- The yield was 1.36 times that of AL. Simultaneously, HPF fluorescence was monitored to measure the •OH origin from the oxidation of water under radiation, and the results showed that NTAL's •OH generation efficiency was 1.72 times that of AL. In summary, NTAL exhibits excellent free radical generation ability in aqueous solution, which endows it with potential applications in both type I and type II PDTs.
[0104] Preparation and characterization of NTALG
[0105] We used a simple mixing method to mix NT and AL with F127 separately and packaged them into a dual-channel spray device (see reference). Figure 8 In, such as Figure 2 As shown in Figure A, scanning electron microscopy revealed that the hydrogel possesses a porous structure with similar pore sizes. This porous structure endows NTALG with good breathability, which positively promotes skin wound healing. Pranick 127, as a temperature-sensitive hydrogel, is liquid at low temperatures and gradually transforms into a semi-solid gel state as the temperature rises. We explored the gelation behavior of NTALG at five F127 ratios (10%, 15%, 17%, 25%, and 30%) at 20°C and 35% of the body surface temperature. Figure 6 The study screened out hydrogel formulations that could be sprayed under freezing or room temperature conditions and solidify upon adhering to the skin surface, ultimately selecting F127 with a 17% hydrogel and 17% NTALG content. Figure 2C clearly shows that after optimizing the NTALG ratio, the hydrogel is in a liquid state at 20°C, and when the bottle is inverted, the hydrogel remains at the bottle opening. However, at 35°C, the hydrogel is in a solid state, and when the bottle is inverted, the hydrogel remains at the bottom. This phenomenon indicates that 17% NTALG can transform from a liquid state at room temperature to a semi-solid state at 35°C. This characteristic fully demonstrates the extremely high sensitivity of 17% NTALG to temperature changes and also suggests that NTALG at this concentration can solidify at body surface temperature. The gelation behavior of other concentrations of F127 is as follows... Figure 6 As shown, F127 at 10% and 15% concentrations remained liquid at 20°C and 35°C, failing to gel at body temperature. Hydrogels with 25% and 30% F127 concentrations exhibited a gel state at both 20°C and 35°C, indicating that spraying functionality was not feasible. Therefore, we selected a hydrogel with 17% F127 and 17% NTALG. The unique orange-red fluorescence of AQPP under UV irradiation indicates that the liposomes AL carrying the photosensitizer AQPP were successfully encapsulated within the hydrogel and stably performed their function. Figure 2 D and Figure 2 The comparison showed that 17% Pluronic 127 hydrogel and 17% NTALG hydrogel exhibited similar gelation temperature and elastic modulus, indicating that the addition of NTAL did not alter the inherent properties of Pluronic 127 hydrogel. Considering the need for spray application for subsequent drug delivery and referencing the widespread application of NTAL in related fields by other researchers, this study ultimately selected a 17% NTALG hydrogel concentration for subsequent experiments. To investigate whether the function of NT encapsulation in F127 hydrogel was affected, and to further investigate whether the oxygen generated by NT could reach the wound surface through diffusion, the research team explored the dissolved oxygen content of the upper deoxygenated PBS at different time points after the hydrogel solidified. Figure 2 F indicates that after 8 minutes of xenon lamp irradiation, NT-Gel produced an oxygen concentration of 1.5 mg / L, while NTALG produced an oxygen concentration of 0.86 mg / L. This may be because, under xenon lamp irradiation, AL utilizes some of the oxygen produced by NT to generate reactive oxygen species.
[0106] Given that the pH value of the wound surface may affect the healing process, the research team further investigated the drug release rate of AL in 17% NTALG under different pH conditions (pH 4.5, pH 7.5, and pH 8.5). As shown in Figure 2G, in a normal physiological environment (PBS, pH = 7.4), the AL release from the NTALG hydrogel reached 40% after 4 hours; while in acidic (PBS, pH = 4.5) or alkaline (PBS, pH = 8.5) environments, the AL release was approximately 33% and 53% after 2 hours, respectively, indicating a high drug release rate in the first 8 hours. After 12 hours, the drug release approached 100% in acidic or alkaline environments (PBS, pH = 4.0 or pH = 8.9); at the 12-hour time point, the drug release under normal physiological conditions was approximately 95% (PBS, pH = 7.4). It is worth noting that the drug release rate of NTALG hydrogel is slightly higher in an alkaline environment than in a normal physiological environment. This also reflects that NTALG hydrogel exhibits a certain degree of responsive drug release under the high pH conditions of diabetic chronic inflammatory wounds. To evaluate the effect of NTALG's oxygen production function on cell migration, we performed a scratch assay on Hacat cells. Figure 2 The results showed that under light conditions, both NTALG and AL-Gel had a positive effect on cell migration, while AL-Gel inhibited Hacat cell migration by consuming oxygen in the culture medium. To assess biocompatibility, the NTALG hydrogel system was also subjected to a cytotoxicity test using human umbilical vein endothelial cells (HUVECs). Figure 2 H), and at the same time, our research team explored the cytotoxicity of different concentrations of NTALG (H). Figure 2 I), and finally NTALG at a concentration of 40ug / mL was selected for subsequent antibacterial tests.
[0107] Example 2: Investigation of the antibacterial and in vivo diabetic wound healing capabilities of NTALG
[0108] The NTALG described in this example was prepared according to the preparation method in Example 1, wherein the concentration of Pluronic F127 was 17 wt%, and NT hydrogel and AL hydrogel were obtained.
[0109] The simplest molar ratio of the four components in total lipids is 1:1:1:0.05.
[0110] S2: NT hydrogel and AL hydrogel were mixed in a 1:1 volume ratio using a dual-channel spray bottle at approximately 10°C and a pressure of about 0.1-0.3 bar, forming in situ on a surface at 35°C. The hydrogel was then stored in a refrigerator at 4°C overnight to allow it to fully swell.
[0111] 1. Antibacterial properties
[0112] The antimicrobial activity of NTAL hydrogel was evaluated using a plate counting strategy. First, 1 mL of *Escherichia coli* or *Staphylococcus aureus* (colony-forming units per mL) was incubated with NTAL hydrogel at 37°C for 12 hours. For the laser-treated group, the NTAL hydrogel was irradiated with 60 mW light for 5 minutes. Then, 0.1 mL of the bacterial suspension was plated onto agar and incubated at 37°C for 24 hours. Finally, the number of bacterial colonies was determined, and their antimicrobial activity was assessed. To further demonstrate the antimicrobial activity of NTAL hydrogel, scanning electron microscopy (SEM) images of bacterial morphology under different treatments were examined.
[0113] Establishment of an infectious diabetic wound model
[0114] To evaluate the therapeutic effect of NTAL hydrogel, a mouse model of infectious diabetic wounds was established. Male C57BL / 6J mice weighing 25-30 grams were selected, fasted for 12 hours, and then intraperitoneally injected with streptozotocin (100 mg / kg). Mice were kept anesthetized during the intraperitoneal injection. Three days after the first injection, blood glucose levels were measured for two consecutive days. Mice with a blood glucose level exceeding 16.1 mmol / L were identified as diabetic mice. The diabetic mice were anesthetized with isoflurane, and their dorsal hair was completely shaved. A full-thickness wound was then created using a 10 mm diameter skin biopsy punch, and 10 μL of Staphylococcus aureus suspension (colony-forming units per ml) was dripped onto the wound surface to establish an infectious wound model. Mice were kept anesthetized during this process. Two days after infection, the bacterial colony count increased from [number missing] to [number missing] colony-forming units, indicating successful establishment of the infection model.
[0115] Healing of infectious diabetic wounds
[0116] After establishing an infectious diabetic wound model, hydrogel solutions, including hydrogels of various types such as NT hydrogel, AL hydrogel, or NTAL hydrogel, were drop-applied to the wound. The hydrogel liquid was sprayed to rapidly cover the entire wound area, and then cured by heating with skin surface temperature. Mice were kept anesthetized during hydrogel application and photocuring. PBS was used to treat the wound as a control group. Subsequently, wounds covered with different hydrogels were exposed to a xenon lamp at an intensity of 60 mW / cm² for 5 minutes. For the next 3 days, mice were anesthetized with isoflurane and the wounds were irradiated with a xenon lamp at an intensity of 60 mW / cm² for 5 minutes daily.
[0117] Experimental results:
[0118] 1. In vitro anti-MRSA and anti-Ecoli activity of NTALG
[0119] Two representative pathogenic bacterial strains, methicillin-resistant Staphylococcus aureus (MRSA, American Type Culture Collection (ATCC) 43300) and Escherichia coli (E. coli, ATCC 25922), were selected to verify the antibacterial activity of NTALG. During the experiment, a concentration of approximately 10... 8 MRSA or Escherichia coli at colony-forming units (CFU) / mL were co-incubated with NTALG in a saline solution containing 10 mM glucose for 2 hours under specific conditions. Compared to other groups, NTALG achieved a 99% inhibition rate against MRSA under specific light conditions. Figure 3 A and Figure 3 B), the inhibition rate against Ecoli reached 90% ( Figure 3 E and Figure 3 F). Bacteria stained with SYTO9 / PI were studied using confocal laser scanning microscopy (CLSM), and the results were consistent with those of bacterial smear assays. Figure 3 C and Figure 3 E). In addition, scanning electron microscopy was used to observe bacterial morphology in order to confirm the bactericidal effect of NTALG after light exposure. Figure 3 D and Figure 3 H showed that in the NTALG group, MASA and E. coli bacteria exhibited rough surface topology, indicating that NTALG caused damage to bacterial membrane function after light exposure, suggesting that it has a strong antibacterial effect.
[0120] 2. NTALG's in vivo diabetic wound healing ability
[0121] In vitro experiments showed that NTALG, with its antibacterial activity and good biocompatibility, has potential application value in wound management. A mouse model of full-thickness skin defects infected with methicillin-resistant Staphylococcus aureus (MRSA) was used. Histological evaluation of the wound was performed on postoperative days 3, 5, 7, and 14. A 10 mm diameter wound was set up, and local treatments were administered with saline, AL-Gel, NT-Gel, and NTALG, respectively, along with xenon lamp irradiation (experimental procedures detailed in [link to experimental protocol]). Figure 4Figure 4B shows the wound healing kinetics curves of different treatment groups. The control group showed obvious inflammatory response on day 5, while the NTALG hydrogel phototherapy group (NTALG-L group) showed a significant reduction in inflammation (p < 0.05). The wound closure speed of the NTALG-L group was significantly better than that of other experimental groups, especially on day 5 (p < 0.05). By day 14, the wounds of the NTALG-L group and the AL-Gel-L group had basically healed, and the wound area on days 4 and 15 was significantly smaller than that of other treatment groups (p < 0.05). Histological evaluation was carried out by hematoxylin-eosin staining (H&E), Masson's trichrome staining, and CD31 immunohistochemical analysis. The re-epithelialization process was quantified by measuring the width of the epithelial gap and the thickness of the granulation tissue. Hematoxylin-eosin staining (H&E) analysis showed that the regenerated tissue showed the characteristics of complete re-epithelialization of the acute wound on postoperative day 12 (p < 0.05). Figure 4 EF, Figure 4 I). Masson staining results showed ( Figure 4 G and Figure 4 In the late healing stage, the NTALG-L and AL-Gel-L groups formed deep blue collagen fibers, indicating high collagen maturity; while other groups showed light blue fibers, suggesting that the infected wound was still in the repair stage. Notably, the NTALG-L group showed extensive hair follicle regeneration, demonstrating its advantage in promoting tissue remodeling. Histological results were highly consistent with wound healing kinetics data. Weight monitoring results (Figure 4D) showed that the NTALG-L group maintained significantly better weight than other experimental groups (p < 0.05), indicating good systemic safety of the material. Bacteriological analysis showed that the bacterial survival rate of the wound in both the NTALG-L and AL-Gel-L groups was less than 13% on day 7 (p < 0.05, Figure S2B). Simultaneously, immunohistochemical results showed that the wound in the NTALG-L group had richer blood vessels than other groups (p < 0.05). The above results collectively confirm that NTALG demonstrates excellent potential for treating infected wounds by accelerating wound closure, promoting collagen deposition and reepithelialization.
[0122] 3. NTALG Biosafety Assessment
[0123] To further assess the biosafety of NTALG, we performed H&E staining on major organs and conducted blood analyses to investigate whether mice experienced systemic side effects after NTALG administration, such as tissue damage, inflammation, lesions, and excessive immune responses. As shown in Figure 5A, complete blood counts and biochemical analyses were performed on different treatment groups, covering white blood cells (WBC), red blood cells (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular hemoglobin (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red blood cell distribution width (RDW), creatinine (CREA), blood urea nitrogen (UREA), alanine aminotransferase (ALT), and aspartate aminotransferase (AST). Compared with the control group (CON), the NTALG group showed no significant changes in complete blood counts and biochemical indicators, indicating no liver or kidney damage. Figure 5 B shows that, compared with the control group (CON), no significant pathological abnormalities were observed in H&E staining (heart, liver, spleen, lungs, and kidneys) in the NTALG group. In summary, the NTALG described in this invention exhibits good in vivo biocompatibility.
[0124] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A sunlight-excited, multi-ROS-responsive, oxygen-sensitizing hydrogel, characterized in that, It was prepared from plant-derived nanothylakoids (NTs) and liposomes (ALs) loaded with 2-(4-(1,6,9-triphenyl-3a,11b-dihydro-1H-phenanthro[9,10-d]imidazol-2-yl)phenyl)anthracene-9,10-dione (AQPP), with Pranic F127 as the hydrogel matrix.
2. The hydrogel according to claim 1, characterized in that, The nano-thylakoids are derived from spinach.
3. The hydrogel according to claim 1, characterized in that, The method for preparing the AQPP-loaded liposomes includes the following steps: The four components of total lipids are mixed in tetrahydrofuran (THF) solvent according to the simplest molar ratio, and AQPP is added simultaneously to obtain a mixed solution. In the mixed solution, the concentration of total lipids is 0.1-20 mg / mL, and the concentration of AQPP is 0.1-10 mg / mL; preferably, the concentration of total lipids is 1-3 mg / mL, and the concentration of AQPP is 0.5-2 mg / mL. Perform ultrasonic treatment; Add the obtained solution dropwise to deionized water while stirring continuously; Remove tetrahydrofuran, filter, and you have the product.
4. The hydrogel according to claim 1, characterized in that, The simplest molar ratio of the four components in total lipids—dioleoyltrimethylammonium chloride (DOTAP), dioleoylphosphatidylethanolamine (DOPE), cholesterol, and dioleoylphosphatidylethanolamine-polyethylene glycol 2000 (DOPE-PEG2000)—is (0.25-2):1:1:0.
05. The preferred ratio is 0.25:1:1:0.05; 0.5:1:1:0.05; 1:1:1:0.05; 2:1:1:0.05; The optimal ratio is 1:1:1:0.
05.
5. The method for preparing the photoexcited multi-ROS responsive oxygen-sensitizing hydrogel according to claim 1, characterized in that, Includes the following steps: S1: Disperse the nano-thylakoids (NT) in deionized water at a concentration of 10 μg / mL to 400 μg / mL to obtain an NT aqueous solution, and add Pluronic F127 to obtain an NT hydrogel; Liposomes (AL) were dispersed in deionized water at concentrations of 10 μg / mL to 1000 μg / mL to obtain an AL aqueous solution. Prönkel F127 was then added to obtain an AL hydrogel. S2: NT hydrogel and AL hydrogel are sprayed together in a volume ratio of 1:1 at a temperature range of 4℃-25℃ and formed in situ on the surface at 34℃-36℃.
6. The preparation method according to claim 5, characterized in that, In the NT hydrogel and AL hydrogel, the content of Pranic F127 is 10wt%-25wt%, preferably 15wt%-25wt%, and more preferably 17wt%-20wt%.
7. The preparation method according to claim 5, characterized in that, In the NT aqueous solution, the concentration of NT is 80 μg / mL to 120 μg / mL, and in the AL aqueous solution, the concentration of AL is 100 μg / mL to 300 μg / mL.
8. The preparation method according to claim 5, characterized in that, The spray mixing described in step S2 is carried out in a dual-channel spray bottle.
9. The use of the sunlight-excited multi-ROS-responsive oxygen-sensitizing hydrogel according to any one of claims 1-4 in the preparation of a medicament for treating skin ulcers.
10. The application according to claim 9, characterized in that, The skin ulcer is a diabetic foot ulcer.
Citation Information
Patent Citations
I-type photosensitizer with AIE property, nano-particles, preparation method of I-type photosensitizer and nano-particles and application of I-type photosensitizer and nano-
CN118271247A
Cited By
Photo-activated myocardial targeting nano capsule for heart failure
CN122031418A